Do investors get an advantage from corporate green bond issuance? A cross-country study - Riaz, Tabassum; Selamat, Aslam Izah; Mohd Nor, Normaziah; Sheikh Hassan, Ahmad Fahmi (Sciendo, 2025)
This study examines the stock's response to corporate green bond issuance announcements. Analyzing a dataset of 230 global corporate green bond issuers from 38 countries between 2013 and 2022 through an event study, the findings reveal a positive market reaction, especially within the non-financial corporate sector. Green bonds in this sector are primarily used to fund their own eco-friendly projects, signaling a commitment to environmental sustainability, and generating investor confidence. Variation in market reactions across countries is noted, with developed countries exhibiting a significantly more positive response. This suggests that environmental initiatives hold greater value in these regions, highlighting the alignment between sustainable practices and investor sentiment. These results emphasize the potential advantages of integrating green bonds and their environmental commitments into investment strategies, particularly for portfolio diversification and attracting investors seeking sustainable opportunities.